A programme to spread eGFR graph surveillance for the early identification, support and treatment of people with progressive chronic kidney disease (ASSIST-CKD): protocol for the stepped wedge implementation and evaluation of an intervention to reduce late presentation for renal replacement therapy - Gallagher, Hugh (BMC Nephrol, 2017)
BACKGROUND: Patients who start renal replacement therapy (RRT) for End-Stage Kidney Disease (ESKD) without having had timely access to specialist renal services have poor outcomes. At one NHS Trust in England, a community-wide CKD management system has led to a decline in the incident rate of RRT and the lowest percentage of patients presenting within 90 days of starting RRT in the UK. We describe the protocol for a quality improvement project to scale up and evaluate this innovation. METHODS: The intervention is based upon an off-line database that integrates laboratory results from blood samples taken in all settings stored under different identifying labels relating to the same patient. Graphs of estimated glomerular filtration rate (eGFR) over time are generated for patients <65 years with an incoming eGFR <50 ml/min/1.73 m(2) and patients >65 years with an incoming eGFR <40 ml/min/1.73 m(2). Graphs where kidney function is deteriorating are flagged by a laboratory scientist and details sent to the primary care doctor (GP) with a prompt that further action may be needed. We will evaluate the impact of implementing this intervention across a large population served by a number of UK renal centres using a mixed methods approach. We are following a stepped-wedge design. The order of implementation among participating centres will be randomly allocated. Implementation will proceed with unidirectional steps from control group to intervention group until all centres are generating graphs of eGFR over time. The primary outcome for the quantitative evaluation is the proportion of patients referred to specialist renal services within 90 days of commencing RRT, using data collected routinely by the UK Renal Registry. The qualitative evaluation will investigate facilitators and barriers to adoption and spread of the intervention. It will include: semi-structured interviews with laboratory staff, renal centre staff and service commissioners; an online survey of GPs receiving the intervention; and focus groups of primary care staff. DISCUSSION: Late presentation to nephrology for patients with ESKD is a source of potentially avoidable harm. This protocol describes a robust quantitative and qualitative evaluation of a quality improvement intervention to reduce late presentation and improve the outcomes for patients with ESKD.